"Meille tulee aina riittämään ruokaa" : ruokahävikille annetut kulttuuriset merkitykset lukiolaisten arjessa - Honkanen, Tuomi (2020)
I studied four Finnish high school students and the different cultural meanings that they are giving to food waste in their everyday life. In this bachelor’s dissertation I aimed to find out what kind of food waste my informants face in their everyday life and how they think about food waste. Do they for example see food waste to be a moral, environmental or economic problem? I also aimed to gather some research data about how those different cultural and moral values associated with food can affect food waste. My main research question was: “What kind of cultural values people are associating with food waste”?